The dynamics of spermatogenesis in the European bitterling (Rhodeus amarus Bloch, 1782) from the Zaporizhzhia (Dnipro) Reservoir - M. Yerukh; O. Marenkov (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To investigate the peculiarities of spermatogenesis in the European bitterling (Rhodeus amarus) in the conditions of the Zaporizhzhia (Dnipro) Reservoir, to determine the ratio of gametes of different stages of development and to establish their morphometric parameters.